TINJAUAN HUKUM ISLAM TENTANG PELAKSANAAN PINJAMAN DENGAN JAMINAN EMAS PADA PEMBIAYAAN MULIA DI PEGADAIAN SYARIAH - Hidayatina, Hidayatina (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2016)
This research aimed at figuring out the regulations of Islamic laws in dealing with loans and gold as warranty on Mulia Financing in Islamic pawnshop. To achieve the desired aim, this study employed normative study by applying qualitative approach. Furthermore, conceptual approach which was dealing with multi-agreements in Islamic law was used to figure out the implementation loan using gold as warranty on Mulia Financing in Islamic pawnshop according to Islamic laws. The data of the research were the secondary ones which were obtained from books, internet resources and previous relevant studies and collected through library research. The data were analyzed by means of normative analyisis and study based the available data. The findings showed that the implementations were not suitable with Islamic laws due to the absence of the requirement for the objects of loan. Furthermore, multi-agreement practices which are prohibited in Islam also took place.